The handbook of sexuality in close relationships - Harvey, John H., 1943-; Wenzel, Amy; Sprecher, Susan, 1955- (Lawrence Erlbaum Associates, Publishers, 2004)
"Although sexuality is an integral part of close romantic relationships, research linking these two constructs has been less systematic than other areas pertaining to close relationships. To date, researchers in communication, sociology, family studies, psychology, and psychiatry, have made significant advances in both of these fields. The editors' goal is to integrate this research into one volume. They bring together major scholars from the diversity of fields working on close relationship topics to examine past contributions and new directions in sexuality. The emphasis is on theoretical integration and stimulation, methodological rigor, and critical analysis. This volume explores early sexual experiences and their impact on late life sexuality, how life's stresses impact sexuality and satisfaction with closeness, the affect of postpartum depression on sexuality, and the relationship between control, power, anger, as well as revenge and sexual processes in couples"--Publisher's description